The classification of ethnic groups in ancient China - Wang, Wenguang 1955-; Duan, Hongyun 1975- (Peter Lang, 2023)
"Ethnic classification is the process of establishing standards for the characterization of ethnic group composition and identifying their ethnonyms. According to relevant conclusions of archaeology and historical, cultural and linguistic materials of various ethnic groups in ancient literature, the ethnic names and ethnic compositions are identified by certain ethnic groups in different parts of ancient China. The geographic regions where ethnic groups developed served as the spatial scope, and the timeline of Chinese historical periods and dynasties served as the temporal sequences for this study. The book examines the relationship between the culture of the Neolithic Age and the early people's community, and then analyzes the ethnic groups mentioned in historical literature and their cultural relationships. In addition, according to different historical periods, the names of ethnic groups appearing in each region are examined. The relationships between the names of these ethnic groups and related ethnic groups in the previous and the following historical periods are explored, and it is examined whether different national names in different periods were in the nationality shared intrinsic commonality. Therefore, these studies have used national ideology to guide ethnic identifications in ancient China. It shows how the Chinese people developed their civilization and eventually formed the great majority of today's ethnic communities on their own land"--